The impact of participation in extra-curricular physical activity on males from disadvantaged schools. (February 2017) - Belton, Sarahjane; Prior, Paul; Wickel, Eric; Woods, Catherine
Extra-curricular physical activity (ECPA) may have an important role to play in the health and well-being of adolescents, but the actual benefits are relatively unknown. This study examined ECPA participation amongst adolescent males (age 12–15 years) from disadvantaged backgrounds, and evaluated its impact on overall physical activity (PA) accumulation and psychological well-being. At three time points over a single academic year, participants from four schools ( n = 174) wore a pedometer for seven days and completed a questionnaire assessing habitual PA, frequency of ECPA participation, barriers to ECPA participation and seven psychosocial subscales. An average year-long score was calculated for each participant, for each variable. Across seasons, 84% of participants reported regular (≥ twice a week) or occasional (once a week) participation in ECPA. Those reporting regular participation in ECPA were significantly ( p < .01) more active (steps/day) and scored higher ( p < .01) on each psychosocial subscale. Results of multinomial regression analysis showed that perceived physical competence ( p < .001) had a significant main effect on ECPA participation. Our study results indicate that students from disadvantaged backgrounds whom participate in ECPA at least once a week are significantly more physically active and have a higher level of psychological well-being than those who never participate.